PTH-131 Current Gastroenterology Teaching in UK Medical Schools: A BSG Survey. (17th August 2016) - Cheung, VTF; Johnson, GJ
Abstract : Introduction: Little is known about undergraduate gastroenterology teaching in the UK. This project aims to inform how the BSG could assist with undergraduate teaching, and ultimately inspire future doctors to choose a career in gastroenterology. Methods: A survey of 27 questions related to undergraduate gastroenterology training was compiled on surveymonkey.com. It was disseminated via the BSG newsletter and through emails to gastroenterology champions involved in undergraduate teaching. In 10 weeks, 91 representatives from 26 medical schools filled out the survey. Results: Students per year group ranged from 30–400. 49% had an integrated curriculum, 44% had traditional (preclinical then clinical) and 7% unsure. 43% medical students undertook at least one block on a gastroenterology/hepatology firm, 43% didn't and 14% unsure. Gastroenterology blocks lasted between 1 to 10 weeks, were usually undertaken from year 3 onwards and some medical schools had them in several years. Only 13% mandated a minimum number of observed procedures- on average OGD 2, colonoscopy 1, liver biopsy 4 and US/CT 4. Gastroenterology training took place in: Primary care 26% Secondary care (wards) 95% Secondary care (clinics) 95% Secondary care (endoscopy) 72% Others (clinical skills lab/seminars) 30% There were extra-curricular opportunities for gastroenterology training- Electives 76%, SSMs 81, BSc 35% and others (Research project, MSc) 16%. Was gastroenterology training integrated with surgical training? Yes 37% No 58% Unsure 5% 88% responded that there was a copy of the Gastroenterology syllabus/set of learning objectives within the MBBS curriculum and of those, 91% had read them. Knowledge of gastroenterology was usually assessed with combination of OSCEs, knowledge based exams (SBA/MCQs) and medical finals. Asked in what year, gastroenterology is assessed: 1 3% 2 3% 3 15% 4 6% 5 or 6 (final) 18% All years 29% Mixture of years 26% Did the medical school have a student gastroenterology society? Yes 11% No 63% Unsure 26% Only 60% were willing to send out a questionnaire to their medical students. Conclusion: Some students did not have a dedicated gastroenterology block and some blocks were only for 1 week. It is unclear whether this is sufficient time to build up an interest in gastroenterology so this is an area where the BSG can assist in developing gastroenterology training. There were questions skipped by doctors completing the survey, reflecting the fact that they may not be aware of the specifics of curriculum development. This emphasises the importance of involving these trainers in curriculum development at a university level if change is to happen. Some respondents expressed an interest in how to start a student gastroenterology society and this may be an avenue for BSG to develop links and attract students towards a career in gastroenterology. Disclosure of Interest: None Declared